Optimization of Seed Dormancy-Breaking and Wood Vinegar Application for Enhancing Podocarpus blumei Seedling Performance - Noviyanti, Ayu; Prameswari, Diana; Prasetyorini, Prasetyorini (Journal of Science Innovare, 2025)
Podocarpus blumei is a slow-growing coniferous tree species belonging to the Podocarpaceae family, widely utilized for timber, handicrafts, and traditional medicine in Indonesia. However, its propagation remains limited due to seed dormancy and low germination rates. This study aimed to determine the most effective combination of seed dormancy-breaking techniques and wood vinegar concentrations to optimize seed germination and early seedling growth. The experiment was conducted using a completely randomized design with factorial treatments involving different dormancy-breaking methods—scarification, soaking in coconut water, and hot water—and variations in planting media (soil, cocopeat, and husk charcoal). Subsequent seedling treatments involved applying wood vinegar at four concentrations (0%, 0.1%, 0.2%, and 0.3%) for eleven months. Results showed that P. blumei seeds had an average moisture content of 40.14%, classifying them as recalcitrant. Among the dormancy-breaking treatments, scarification produced the highest germination rate (90%), maximum growth potential (92%), and fastest germination period (51 days) in soil–cocopeat–husk charcoal media. Application of 0.2% wood vinegar significantly increased stem diameter (0.8 mm), leaf number (19), and biomass accumulation, indicating enhanced physiological activity. In contrast, higher concentrations (≥0.3%) did not further improve seedling performance. The findings demonstrate that integrating mechanical scarification and moderate wood vinegar concentration (0.2%) effectively enhances the germination and early vigor of P. blumei seedlings. This study provides a practical propagation approach for conserving and sustainably managing Podocarpus blumei populations, contributing to improved silvicultural practices for native forest species in Indonesia.